Mean laydate per species per year (1961-2012) - Kluen, Edward; Nousiainen, Riikka; Lehikoinen, Aleksi (Dryad Digital Repository, 2016)
Laydates for 26 common breeding bird species in Finland were estimated based on nest-card data. The data here contains mean laydates (and standard deviation) per bird species per year for the period 1961-2012, including the number of nestcards on which each mean laydate was based on.